An umbrella systematic review of antibiotics therapy in COVID-19 patients: implications for antimicrobial resistance - Irfan, Omar; Amjad, Aqsa; Qadir, Muskaan Abdul; Zakaria, Maheen; Rehman, Alishba; Rehman, Abdul; Hammad, Muhammad Bin; Zubairi, Ali Bin Sarwar; Khan, Javaid Ahmed (International Journal Of Community Medicine And Public Health, 2025)
Evidence from public health bodies describes extensive overuse of antibiotics during the COVID-19 pandemic worldwide, further worsening the spread of antimicrobial resistance (AMR). Umbrella review (CRD42024590181) of SRs that investigated the safety and efficacy of antibiotic drug therapies for treatment in COVID-19 patients irrespective of disease severity and age was conducted. Comprehensive searches were conducted between July 30, 2024, and October 26, 2024, covering PubMed and Cochrane databases, and other sources, such as, Coronavirus (COVID-19) Cochrane resources, and Google Scholar. The AMSTAR2 tool was used to assess the methodological quality of the included SRs. Review findings were synthesized narratively. The systematic search yielded a total of 3624 records from the electronic databases search. Ten original SRs, with 1-42 studies in each SR, were finally included. Sample size per SR ranged from 665-37,429 patients. Azithromycin was the most commonly administered antibiotic therapy. Overall, the studies included in this review reported no difference in all-cause mortality, time to clinical recovery, length of hospital stay, progression to severe disease, viral clearance, rate of co-infections or superinfections, and adverse events among patients treated with antibiotics compared to placebo/standard of care. Evidence suggests that use of antibiotics in COVID-19 patients is not associated with better outcomes. Further studies assessing prevalence of AMR and antibiotic usage during COVID-19 infection could aid in improving antimicrobial stewardship in clinical practice.